A DESIRABLE LEADER: REFLECTION OF THE POPULIST CHARACTERISTICS - S. B. Pramono and Dessy Harahap; Amalia Irfani (Al-Albab, 2013)
There is no country that is successful in its management without intervention of a leader. The leader is the spearhead of the success of a country. The thought, effort, even the habit of the leader are capable of making people follow and treat them like an idol figure/a celebrity. A successful leader will always be honored while those who fail will usually be scorned and even removed.